AVALIAÇÃO DO DESEMPENHO E ESTUDO DA VIABILIDADE ECONÔMICA DA GERAÇÃO DISTRIBUÍDA POR SISTEMAS FOTOVOLTAICOS CONECTADOS À REDE ELÉTRICA - Silveira, Camila; Tonolo, Edwin; Krasnhak, Larissa; Urbanetz Jr, Jair (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Humanity is increasingly dependent on energy and the demand for it is growing every day. Renewable energy sources are consolidated alternatives in the market. Governmental incentives have been created to stimulate the installation of small scale systems. Despite the great advantages of renewable sources, a preliminary study of the locations to be installed the systems is of high importance. Technical and economic studies must be taken into account, so the system will not be installed in a non-beneficial place and may not generate the desired energy and became not profitable. A study in two different photovoltaic (PV) systems will be performed. The figures of merit (Performance Ratio, Yield and Capacity Factor) give the comparison of PV system installed in different places, positions and inclination angle. The economic scenario, calculated by the payback period and discount payback period and also internal rate of return (IRR) and net present value (NPV) can indicate the investment viability. The average monthly energy consumption was considerate, an estimated value for the energy price, in 25 years, had to be calculated, the maintenance and efficiency loss were taken into account. The payback period estimates a smaller time than the discounted payback, in both studied systems.